2009
DOI: 10.1111/j.1528-1167.2008.01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 is associated with resistance to febrile seizures: Genetic association and experimental animal studies

Abstract: SUMMARYPurpose: Febrile seizures (FS) are the most common form of childhood convulsions. Many reports have shown that a proinflammatory cytokine, interleukin-1 (IL-1) b, may have a facilitatory effect on the development of FS. We have previously shown that the IL1B -511C/T single nucleotide polymorphism (SNP) is associated with simple FS of sporadic occurrence. The balance between proand antiinflammatory cytokines influences the regulation of infections and could, therefore, play a role in the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 49 publications
3
46
0
1
Order By: Relevance
“…8 Interleukin-10 is genetically associated with febrile seizures, and the seizure threshold temperature in interleukin-10-administered rats has been shown to be significantly higher than that in saline-treated controls resistance to seizures. 9 Of all the studied cytokines, only interleukin-6 was significantly correlated with febrile seizures in multivariate analysis. Interleukin-6 has been shown to exert neurotrophic 10-11 and neuroprotective effects.…”
Section: Discussionmentioning
confidence: 98%
“…8 Interleukin-10 is genetically associated with febrile seizures, and the seizure threshold temperature in interleukin-10-administered rats has been shown to be significantly higher than that in saline-treated controls resistance to seizures. 9 Of all the studied cytokines, only interleukin-6 was significantly correlated with febrile seizures in multivariate analysis. Interleukin-6 has been shown to exert neurotrophic 10-11 and neuroprotective effects.…”
Section: Discussionmentioning
confidence: 98%
“…Straussberg et al have shown increased lipopolysaccharide-induced IL-10 production by peripheral blood mononuclear cells from children with a history of FS [14]. Ishizaki et al demonstrated an association between the IL-10 gene and resistance to FS [34]. In contrast, Virta et al have reported that no difference in plasma IL-10 level was found between children with and without FS [35].…”
Section: Discussionmentioning
confidence: 86%
“…Auch die alleinige Gabe hoher Interleukindosen kann Anfälle auslösen, und bei Mäusen, die den Rezeptor für In terleukin1β nicht besitzen, ist die hyper thermiebedingte Auslösung von Anfäl len erschwert [7]. Bei anderen Interleu kintypen wurden jedoch auch entgegen gesetzte Effekte gefunden: Die Schwel le für Hyperthermieanfälle wurde in Rat ten nach Interleukin10Gabe erhöht [12], und Interleukin6 verminderte das Auf treten, verlängerte das Interval bis zum Auftreten und verkürzte die Dauer epi leptiformer Anfälle, die durch Erhöhung der Körpertemperatur bei Ratten ausge löst worden waren [8]. Diese Untersu chungen deuten darauf hin, dass neben der Körpertemperaturerhöhung bei Fie ber körpereigene Substanzen im Allge meinen und das Gleichgewicht der ver schiedenen Interleukine im Besonderen eine zusätzliche Rolle bei der Entstehung von Fieberkrämpfen spielt.…”
Section: Weitere Fieberfaktoren Als Mögliche Ursache Von Fieberkrämpfenunclassified